Sustainable urban and regional infrastructure development : technologies, applications and management - Yigitcanlar, Tan (Information Science Reference, an imprint of IGI Global, 2010)
"This book aims to bridge the gap in the current literature by addressing the overall problems present in major infrastructure in society, and the technologies that may be applied to overcome these problems" (Poskytuje vydavateľ)